Ergonomics awareness and employee performance: An exploratory study - Segun Oluwaseun Olabode; Atinuke Regina Adesanya; Akeem Abayomi Bakare (Economic and Environmental Studies (E&ES), 2017)
The study examined the effects of ergonomics on employee performance by ascertaining the level of ergonomics awareness in Nigerian organizations, identifying the factors hindering the use of ergonomic, and the best practices and methods adopted by various organizations across industries. Despite a knowledge of importance to a growing number of researchers in Nigeria, there is still a dearth in knowledge of ergonomics design and its implementation in Nigeria. This can be observed in the low level of its adoption. The study adopted an exploratory approach through the review of literature. It was seen that several factors have hindered the efficient implementation of ergonomics in Nigeria which ranges from awareness, insufficient relevant studies, personnel considerations, resources constraints, technological changes, communication and integration disconnection between employees and equipment designers. Also, some best practices and methods adopted by various organizations across industries were identified to include, but not limited to: integration of human element into work design, ergonomics maturity levels (reactive, preventive, proactive and advanced) and quality of workspace (office design, furniture and spatial arrangements, lightings and heating arrangements, noise level). It is, however, recommended that researchers in the field of ergonomics and practitioners in the industry should intensify efforts in carrying out relevant study, organizing conferences and seminars as well as media publicity on why ergonomics should be part of our daily activities. It is also recommended that organizations should orientate and train employees on ergonomics so that they will be aware of the benefits derivable from it and be able to fit into the organization's designs. Lastly, they should integrate employee/human element into ergonomics design process by getting detailed anthropomorphic data, which may bridge the communication disconnect between employees and ergonomic designers.
Keywords: J8; J81; 330; Employee performance; Ergonomics awareness; Ergonomics design; Hindrances; Implementation methods and practices